Epidemiological Profile of the Contact Lens Sector of the Benjamin Constant Institute in Rio de Janeiro - Marcos,Alléxya Affonso Antunes (2018)
Abstract Objective: The objective of this project is to describe the epidemiological profile of the Contact Lens Sector of the Benjamin Constant Institute in Rio de Janeiro. Methods: A retrospective study of 788 cases was carried out from March / 2004 to June / 2015. Results: Most of the objects in the cases were female (62.23%). As for the indication, 445 cases (56.47%) were optical, 281 cases (35.65%) were esthetic, 44 cases (5.58%) were prosthetic, and 18 cases (2.30%) were cosmetic. The most prevalent age group was from 20-39 years of age (46.34% of cases), followed by 40-64 years of age (25.31% of cases). Of the total of adapted cases, 81.6% were with rigid lenses, and among the optical medical indications, 61.4% of the cases were by keratoconus. Conclusions: Because it is a reference medical service, whose main objective is the rehabilitation of patients with low vision, the optical medical indication was the most frequent. The rigid lenses showed up with a prominent role in the adaptations.